Fine-scale spatial genetic structure and allozymic diversity in natural populations of Ocotea catharinensis Mez. (Lauraceae) - Tarazi R. (2010)
In order to establish a strategy for conservation, the distribution of genetic diversity in four natural populations of Ocotea catharinensis in the Brazilian Atlantic rain forest was investigated using 18 allozyme loci. Estimates of the average number of alleles per loci (2. 2), percentage of polymorphic loci (83. 3%) and expected genetic diversity (0. 427) in adult individuals were high; suggesting that all populations have genetic potential for conservation. The inbreeding within populations (f = - 0. 011) and the total inbreeding (F = 0. 133) suggest population structure, since a high level of divergence among populations (θP = 0. 143) was also detected. Significant values of spatial genetic structure were found inside the four populations. This study demonstrates that the realized gene flow among the remaining populations of O. catharinensis is not sufficient to stop population divergence due to genetic drift and local selection, which threatens the future viability of this species. © 2009 Springer Science+Business Media B.V.